The role of training in implementing corporate sustainability: A systematic literature review - Anike Sult; Janice Wobst; Rainer Lueg (Corporate Social Responsibility and Environmental Management, 2023)
Our literature review synthesizes the ways in which training (of management and employees) affects the implementation of corporate sustainability (CS) in organizations. We structure the research field according to the determinants of, approaches to, and outcomes of training for CS. We explain current issues in this field and develop a research agenda. We conducted a systematic literature review starting with an initial sample of 1755 empirical studies. Based on their validity, relevance, and reliability, we selected and discussed the 67 seminal sources in this field. We find that several factors foster the use of training. Besides an intrinsic organizational interest in CS, regulation and stakeholder pressure encourage organizations to prioritize training. We identify multiple approaches to and applications of training. Training on CS may be focused or multifaceted, mandated or collaboratively-driven, but it should always be closely aligned with structure and strategic goals, and must be regularly evaluated. The literature shows that such serious and well-designed training is linked to better environmental, social, and economic performance. Our review is the first to address the role and application of training for CS. We contribute a synthesis of empirical evidence in the field, as well as a research agenda. We highlight that practice should not see CS training from the perspectives of compliance or greenwashing, but embrace the opportunity to create a thus far underestimated alignment with strategy and long-term performance.
Keywords: 650; corporate social responsibility; corporate sustainability; sustainability accounting; sustainable development; systematic literature review; training